High prevalence of latent tuberculosis using the QuantiFERON-TB Gold Plus test in Takayasu arteritis - Ana Luisa Souza Pedreira,; Rodrigo Pinheiro Leal Costa,; Josenor Filipe Pitanga Silva,; Mittermayer Barreto Santiago, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate latent tuberculosis using the QuantiFERON-TB Gold Plus method in patients with Takayasu arteritis (TA). Patients and methods: This case-control study included 22 patients with TA (3 males, 19 females; median age: 36.5 years; IQR, 32 to 50 years), 22 healthy individuals (3 males, 19 females; median age: 38.5 years; IQR, 32.5 to 50 years), and 66 patients with diffuse connective tissue diseases (DCTDs) (4 males, 62 females; median age: 41 years; IQR, 29.8 to 54 years). Two control groups were formed: (i) age- and sex-matched healthy individuals and (ii) patients with other DCTDs. Epidemiological data were collected, and the QFT-Plus test was performed. The QFT-plus positivity was compared among the groups. Results: A higher prevalence of QFT-Plus positive cases was observed in the TA group (8/22) than in the healthy control group (1/22) (p=0.020) or in the group with other DCTDs (3/66) (p=0.001). There was a statistically significant difference in the past pulmonary tuberculosis prevalence between the TA and DCTD groups (p=0.013). Conclusion: The prevalence of latent tuberculosis in TA patients (36.4%) was higher than that in both control groups and higher than the prevalence of latent tuberculosis among the general Brazilian population. Although a positive association was found, it is not possible to establish a direct cause-effect relationship. Given the increasing use of anti-cytokine therapies in TA, it is necessary to thoroughly screen patients with TA before initiating immunosuppressive therapy to avoid tuberculosis reactivation.